Lost in policy translation: Canadian minority Francophones and health disparities - Alimezelli, Hubert Tote; Leis, Anne; Denis, Wilfrid; Karunanayake, Chandima (Canadian Public Policy, 2015)
We reviewed Canadian federal, provincial, and territorial policies related to the health of official language minorities (OLMs) and found important provincial and territorial differences as well as policies penalizing OLMs, which thus contribute significantly to health disparities and to the low vitality of OLM communities. These findings suggest the need for more aggressive, hands-on, and concerted federal and provincial/territorial government efforts to address social inequities and health disparities. Increased policy coherence between these levels of government will not only increase the health and vitality of these populations but also help close the disparity gap and lead to better health and well-being for all Canadians.

Determinants of self-rated health of Francophone seniors in a minority situation in Canada - Alimezelli, Hubert Tote; Leis, Anne; Karunanayake, Chandima; Denis, Wilfrid (Linguistic Minorites and Society, 2013)
Résumé La tendance actuelle montre que les institutions des services de santé et les gouvernements répondent de façon inadéquate aux besoins de plus en plus nombreux d’accès aux services de santé par les populations vieillissantes du Canada et d’autres pays développés. Après l’analyse de l’enquête post-censitaire 2006 de Statistiques Canada sur la Vitalité des Minorités de Langue Officielle, cette étude démontre qu’outre l’age, et en plus d’autres déterminants, les barrières linguistiques auxquelles font face les aînés de langue officielle en situation minoritaire affectent davantage l’autoévaluation de leur santé. Cette étude suggère quelques pistes de solution dont la compréhension des réalités contextuelles, l’amélioration de l’environnement linguistique et des services de santé dans la langue minoritaire. Mots-clés : déterminants de la santé, statut minoritaire, santé perçue, minorités linguistiques, aînés Abstract Current trends show that governments and health institutions in Canada and other developed nations are responding inadequately to the growing need for health services of the increasingly aging population. The Analysis of Statistics Canada’s 2006 post-census Survey on the Vitality of Official Language Minorities show that in addition to age and other socio-demographic determinants, linguistic barriers affect the self-rated health of seniors of official languages living in a minority situation. This study suggests among other things a greater understanding of Official language minorities’ contextual realities, the improvement of both the linguistic environment and services in the minority language. Keywords: health determinants, minority status, self-rated health, linguistic minorities, older adults